LPT-Branch and Bound Algorithm in Flexible Flowshop Scheduling to Minimize Makespan - Dana Marsetiya Utama (PROZIMA (Productivity, Optimization and Manufacturing System Engineering), 2018)
This article discussed the problem of flow shop scheduling to minimize the makespan. The purpose of this article is to develop the LPT and Branch And Bound (LPT-Branch And Bound) algorithms to minimize the makespan. The proposed method is Longest Processing Time (LPT) and Branch And Bound. Stage settlement is divided into 3 parts. To proved the proposed algorithm, a numerical experiment was conducted by comparing the LPT-LN algorithm. The result of the numerical experiment shows that LPT-Branch And Bound's proposed algorithm is more efficient than the LPT-LN algorithm.